PERAN BIMBINGAN AKADEMIK TERHADAP KEMANDIRIAN BELAJAR SISWA SEKOLAH DASAR KELAS 4 STUDI KASUS DI MIS KERTIJAYAN - rizaningtya, cintami; Nadia, Risalatin; Azzah, Masykurotun; Anekasari, Rahmi (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2025)
Learning independence is an important skill that needs to be developed from elementary school, but in practice, many students still rely on teacher guidance. This study aims to describe the role of academic guidance in improving the learning independence of fourth-grade students at MIS Kertijayan. The approach used in this study is qualitative with a case study design. The research data were obtained through observations, interviews, and document analysis involving the homeroom teacher and the school principal. The results showed that academic guidance carried out in a planned manner through re-explanation of material, additional exercises, assistance in learning time management, and remedial programs was able to foster student initiative, responsibility, and courage in independent learning. Although several obstacles were still encountered, academic guidance proved to play a strategic role in forming independent learning habits from an early age. These findings confirm that consistent academic guidance is key to strengthening students' independent learning character.